2009
DOI: 10.1073/pnas.0811817106
|View full text |Cite
|
Sign up to set email alerts
|

Dicer-regulated microRNAs 222 and 339 promote resistance of cancer cells to cytotoxic T-lymphocytes by down-regulation of ICAM-1

Abstract: The RNase III endonuclease Dicer plays a key role in generation of microRNAs (miRs). We hypothesized that Dicer regulates cancer cell susceptibility to immune surveillance through miR processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
117
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(124 citation statements)
references
References 39 publications
5
117
1
1
Order By: Relevance
“…Recent data, for instance, have shown that miR29, which is downregulated in brain tumors, plays an important role in downregulation of the expression of B7-H3, a surface immunomodulatory glycoprotein, inhibiting NK cells and T cells [174]. Along a similar line, other data have shown that Dicer by causing maturation of miR-222 and -339 (two suppressors of ICAM-1 expression on tumor cells), decreases the susceptibility of tumor cells to CTL-mediated cytolysis [175]. Furthermore, recent studies underline the potency of local TLR treatment in antiglioma therapy, showing in a murine glioma model that local CpG-ODN treatment restores anti-tumor immunity [176].…”
Section: Reshaping the Tumor Microenvironmentsupporting
confidence: 56%
“…Recent data, for instance, have shown that miR29, which is downregulated in brain tumors, plays an important role in downregulation of the expression of B7-H3, a surface immunomodulatory glycoprotein, inhibiting NK cells and T cells [174]. Along a similar line, other data have shown that Dicer by causing maturation of miR-222 and -339 (two suppressors of ICAM-1 expression on tumor cells), decreases the susceptibility of tumor cells to CTL-mediated cytolysis [175]. Furthermore, recent studies underline the potency of local TLR treatment in antiglioma therapy, showing in a murine glioma model that local CpG-ODN treatment restores anti-tumor immunity [176].…”
Section: Reshaping the Tumor Microenvironmentsupporting
confidence: 56%
“…Expression profiling reports detection of miR-339 in adult hippocampus (Landgraf et al 2007), cervix (Witten et al 2010), placenta (Cummins et al 2006), and in numerous cancers (Kasashima 2004;Landgraf 2007;Stark et al 2010). MiR-339 is reported to regulate ICAM-1 (Ueda et al 2009), BCL6 , and μ-opioid receptor (Wu 2012). Relevant to our interests in KL as an age-related protein, miR-339 is reported to be among only 16 miR upregulated in long-lived humans, showing a 2.37-fold increase in this cohort (ElSharawy et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…MiR-339 is upregulated in glioma cell lines and tissues and its upregulation causes the downregulation of ICAM-1 (Ueda 2009). When ICAM-1 levels are decreased, critical interaction of ICAM-1 with LFA-1 on tumor-specific cytotoxic T cells cannot occur, allowing tumor cell evasion (Ueda et al 2009). Conversely, miR-339 is downregulated in breast cancer and breast cancer cell lines with least expression in the most aggressive and metastatic tumors .…”
Section: Discussionmentioning
confidence: 99%
“…More work is needed to establish the molecular networks that consisted with miRNA and signaling pathways behind this intriguing phenomenon. Previous studies have established that Dicer-dependent miRNAs have essential roles in diverse biological processes including skin development and aberrant miRNA expression is usually associated with Dicer deregulation (Yi et al 2006;Suárez et al 2007;Ueda et al 2009). Furthermore, Yi et al (2006) have demonstrated that by sequencing analysis of miRNA depletion in both Dicer-and DGCR8-null skin, most abundantly expressed skin miRNAs are dependent on both Dicer and DGCR8.…”
Section: Discussionmentioning
confidence: 99%